BREACH OF CONTRACT IN COMMERCIAL GUARANTEE RELATIONSHIPS: AN ANALYSIS OF DISTRICT COURT DECISION NO. 127/PDT.G/2022/PN JKT.PST - Santoso, Angeline Wellvy; Hadiati, Mia (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
This research examines the legal construction of default in commercial guarantee relationships, focusing on the analysis of District Court Decision No. 127/Pdt.G/2022/PN Jkt.Pst. The background arises from the growing complexity of modern business contracts that position guarantors as equivalent to primary debtors, thereby shifting the legal function of guarantees. This research seeks to examine the legal aspects basis of guarantor liability in cases of debtor default and to assess the judicial interpretation trends regarding contractual obligations. The research applies a normative-juridical approach by reviewing primary legal materials, including primary sources like statutes and judicial rulings, along with secondary materials such as legal literature and journals scholarly. The findings indicate that the court adopted a progressive interpretation of the pacta sunt servanda and good faith principles as the basis for imposing liability on guarantors. The decision reflects a paradigm shift from a formalistic to a contextual and proportional approach that prioritizes substantive justice over mere textual certainty. The study concludes that the standardization of commercial guarantee contracts and consistent jurisprudence are essential to ensure balance between creditor protection and guarantor fairness in commercial transactions.